Поетика, структура й сенси замкненого простору ("Повість про санаторійну зону" Миколи Хвильового) - Барабаш, Ю.Я. (Слово і Час, 2019)
“Повість про санаторійну зону” Миколи Хвильового розглядається у двох контекстах –
європейського модернізму перших десятиліть ХХ ст. і українського модернізму 20-х – початку
30-х років. Факт перегуку повісті зі “санаторною” темою в європейських письменників
(Т. Манн, К. Гамсун, С. Моем, Б. Шульц, Г. Гессе) осмислюється як свідчення зосередженості
письменника на замкненому просторі, ознака естетики модернізму. Аналіз зображеного в повісті
замкненого простору провадиться в кількох аспектах: а) сенс метафори “зони”; б) типологія
замкнених просторів; в) межі та помежів'я санаторного континууму; г) композиція текстового
простору; д) структура замкненого простору як Тексту (початок/кінець, бінарні опозиції,
інтертекст). “Story of Sanatorium Zone” by Mykola Khvylovyi, first published in 1924 under the title “Sanatorium
Zone”, has been considered in two interconnected contexts – the one of European modernism of
the initial decades of the 20th century and that of the so-called Ukrainian ‘latent’ modernism of the
1920s – 1930s. The mentioned fact of the story’s relation to the ‘sanatorium’ theme in the works of
European writers (“The Magic Mountain” by T. Mann, “The Last Chapter” by K. Hamsun, “Sanatorium”
by S. Maugham, “Sanatorium under Clepsydra” by B. Schultz, “Health-Resort Visitor” by H. Hesse)
is considered as a testimony of the writer’s concentration on the confined area, which is one of the
conceptual signs of the modernist aesthetics. The analysis of the confined space, shown in the story,
is carried out in several aspects: a) a metaphor of ‘zone’ as a factor of forming the semantic field
of the confined space; b) typology of confined spaces: pragmatic, prophanic, social and historical,
space of memory, existential, mythological, absurdist; c) relation of the sanatorium space to the
out-of-sanatorium one, frontiers and borders, verticals and horizontals, collision ‘inside/outside’;
d) composition of the textual space of the story (frame composition, the beginning and the end as
compositional elements, assembly, principle of counterpoint, doubling of the narration subject; e) the
structure of the confined space as a Text (‘beginning/end’ as structural component, binary oppositions,
intertextuality – ‘autointertext’, intertextual ‘Dostoyevsky’ palimpsest).
The analysis of poetics, structure, and semantics of the confined space in “Sanatorium Zone” gives
the basis for marking the innovative role of the story by Mykola Khvylovyi in the establishment of the
Ukrainian model of modernism.